Tuberculosis infection control measures at health facilities providing tuberculosis services in Nepal (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2018)
Introduction: Globally there were an estimated 10.6 million new tuberculosis patients and 1.7 million deaths from TB in 2016. There is an evidence of tuberculosis transmission at health care settings where health care workers and patients come in contact with people having tuberculosis. This study aims to explore infection control measures at health facilities in terms of administrative, environmental and personal protective measures needed for infection control.Methods: This is a cross-sectional study carried out at 79 health facilities across the country. The study continued for three months starting from January 2018 to March 2018. Trained enumerators from health sciences background collected the information using semi-structured questionnaire. Written consent was obtained prior interview.Results: All the selected health facilities participated in the study. Around 44% of health facilities have infection prevention plan, but very few of them have budgeted for tuberculosis infection control activities. Less than one third of health facilities (24 out of 79 HFs) have provision to separate presumptive tuberculosis patients, however, only 50% (12 HFs) have turned such provision into action. Only 15 HFs (38%) out of 40 HFs having N95 or FPP2 mask for health workers. Around half of the HFs (44%, 35 out of 79) was found to have cross ventilation.Conclusion: Tuberculosis infection plan needs to be developed and implemented by all the health facilities to strengthen administrative, managerial, and environmental and person protective measures of inaction control to minimize the risk of TB transmission at health facilities.